Evolution of Anxiety and Depression in Men during the First Six Months of the COVID-19 Pandemic and Factors Associated with Worsening of Mental Health: Retrospective Longitudinal Study - Ana Lear-Claveras; Alejandra Aguilar-Latorre; Bárbara Oliván-Blázquez; Sabela Couso-Viana; Ana Clavería-Fontán (Journal of Men's Health, 2022)
Background: The Coronavirus disease (COVID-19) pandemic has had a huge impact on the psychological wellbeing of the population, however, few studies have analysed the psychological consequences for the most vulnerable groups, particularly those suffering from depression and anxiety, and specifically in men. The objective of this study is to analyse the changes in a population of men undergoing active treatment for depression or anxiety and factors associated with these changes. Methods: Retrospective, longitudinal and observational study of a population of 28,294 men in northern Spain. The study variables were sociodemographic variables, chronic comorbidities, COVID-19 infection, anxiolytic and antidepressant drug consumption, and use of healthcare resources. These variables were collected from the Primary Health Care electronic records for the two distinct periods (6 months before and 6 months following the end of the lockdown). To compare drug patterns and the use of healthcare resources a paired Student’s T-test was used. To analyse associated factors related to a deterioration of mental disorders, a multivariate logistic regression was performed. Results: In relation to changes in drug patterns, 40% of men saw an increase in at least one Defined Daily Dose (DDD) of their prescribed drugs during the 6 months following lockdown and the number of appointments at health centres and home visits significantly decreased. Factors associated with a deterioration of mental disorders are being under 60 years old, having an income of less than 18,000 euros/year and suffering from more than one comorbidity. Conclusions: The pandemic had a significant impact on men with a previous diagnosis of depression and/or anxiety.